Pengembangan Media Pembelajaran Interaktif Edpuzzle dalam Pembelajaran Sejarah - Purmintasari, Yulita Dewi; Lesmana, Chandra (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2023)
Learning history is one of the most difficult lessons because of the distance in space and time, so it is necessary to present interactive learning media that make historical values more understandable. The development of Edpuzle interactive video learning media in history learning aims to develop learning media and to determine the effectiveness of the product developed. The research process applies the 4D development research method with the stages of Define, Design, Develop and Deseminate. The research instruments are in the form of expert validation sheets, lift sheets and test questions. The results of the media validation show "very good" worthy of being used as a learning medium with an average score of 4.35. Based on table 2, it shows that the results of the validation of material experts average score of 4.33 in the "very good" category. The results of the one to one evaluation show that the average total score is 3.98 in the "good" category. And the results of the small group evaluation show that the total average score is 4.58 in the "very good" category. the results of the effectiveness test using Mann Whitney U on SPSS, obtained the results of a sig (2-tailed) value of 0.011 <0.05 which means Ho is rejected while Ha is accepted which means the use of interactive media has an effect on learning students become more interested and able to think interactive learning media and not boring.Pembelajaran sejarah merupakan salah satu pembelajaran yang sulit karena jauhnya ruang dan waktu, sehingga perlu menghadirkan media pembelajaran interaktif yang membuat lebih memahami nilai-nilai sejarah. Pengembangan media pembelajaran video interaktif edpuzle pada pembelajaran sejarah bertujuan untuk mengembangkan media pembelajaran dan mengetahui efektivitas produk hasil pengembangan. Penelitian menerapkan metode penelitian pengembangan 4D dengan tahapan Define, Design, Develop dan Deseminate. Instrumen penelitian berupa lembar validasi ahli, lembar angkat dan soal tes. Hasil validasi media menunjukkan “sangat baik” layak digunakan sebagai media pembelajaran dengan skor rata-rata 4,35. Berdasarkan tabel 2 menunjukkan bahwa hasil validasi ahli materi skor rata -rata 4,33 dengan kategori “sangat baik”. Hasil evaluasi   one to one menunjukkan bahwa total skor rata -rata 3,98 dengan kategori “baik”. Dan hasil evaluasi small group menunjukkan bahwa total skor rata -rata 4.58 dengan kategori “sangat baik”. hasil uji efektivitas menggunakan Mann Whitney U pada SPSS, didapatkan hasil nilai sig (2-tailed) sejumlah 0,011 < 0,05 yang berarti Ho ditolak sedangkan Ha diterima yang berarti penggunaan media interaktif berpengaruh dalam pembelajaran. siswa menjadi lebih tertarik dan mampu berfikir dengan media pembelajaran yang interaktif dan tidak membosankan.